PENAMBAHAN BAP DAN NAA TEKNIS DALAM MEDIA MS KULTUR JARINGAN ANGGREK - -, Makhziah (MAPETA, 2008)
Synthetic plant hormone saled in many trade mark as Grow Quick (GQ) used for subtitute of cytokinin and auxin ill tissue culture medium of orchid. TIle aim of this study is to know and get concentration of GQ BAP and GQ NAA in MS medium for the most favor of orchid plantlet growth. Research was conducted in Randomized Block Design was replicated three times. Dendrobium 3 months age as Protocorm Like Bodies (plbs) treated in concentration combination of GQ BAP and GQ NAA in MS medium: MO = MS (control), M. = MS + GQ BAP'l ppm, M2 = MS+ GQ BAP 1 ppm + GQ NAA 1 ppm, M3 = MS + GQ BAP 1 ppm + GQ NAA 2 ppm, M4 = MS + GQ BAP 2 ppm + GQ NAA 2 ppm, M, = MS + GQ NAA 2 ppm. The best plantlet growth was showed MS + GQ BAP 1 ppm + GQ NAA 1 ppm on leaves number and root nlunber.GQ BAP and GQ NAA did not affect plantlet length and plantlet number. Key words: tissue culture, orchid, GQ, BAP, NAA